2021
DOI: 10.3390/jcm10245884
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Hypotension Prediction Index Integrated in an Algorithm of Goal Directed Hemodynamic Treatment during Moderate and High-Risk Surgery

Abstract: (1) Background: The Hypotension Prediction Index (HPI) is an algorithm that predicts hypotension, defined as mean arterial pressure (MAP) less than 65 mmHg for at least 1 min, based on arterial waveform features. We tested the hypothesis that the use of this index reduces the duration and severity of hypotension during noncardiac surgery. (2) Methods: We enrolled adults having moderate- or high-risk noncardiac surgery with invasive arterial pressure monitoring. Participating patients were randomized 1:1 to sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
3
31
1
Order By: Relevance
“…Four randomized controlled trials have investigated the Hypotension Prediction Index's preventive effects on hypotension. 2,[15][16][17] Three of these trials, and an additional retrospective study, 18 showed less hypotension in the Hypotension Prediction Index guided group compared to a control group (the trials vary in their outcome definitions and precise management protocols, but the characteristics are beyond the scope of this analysis). 2,16,17 One trial also investigated the effect on postoperative hypotension and found no difference in their primary outcome between the Hypotension Prediction Index-guided group and the standard care group.…”
Section: Effect Of Hypotension Prediction Index In Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four randomized controlled trials have investigated the Hypotension Prediction Index's preventive effects on hypotension. 2,[15][16][17] Three of these trials, and an additional retrospective study, 18 showed less hypotension in the Hypotension Prediction Index guided group compared to a control group (the trials vary in their outcome definitions and precise management protocols, but the characteristics are beyond the scope of this analysis). 2,16,17 One trial also investigated the effect on postoperative hypotension and found no difference in their primary outcome between the Hypotension Prediction Index-guided group and the standard care group.…”
Section: Effect Of Hypotension Prediction Index In Clinical Trialsmentioning
confidence: 99%
“…2,[15][16][17] Three of these trials, and an additional retrospective study, 18 showed less hypotension in the Hypotension Prediction Index guided group compared to a control group (the trials vary in their outcome definitions and precise management protocols, but the characteristics are beyond the scope of this analysis). 2,16,17 One trial also investigated the effect on postoperative hypotension and found no difference in their primary outcome between the Hypotension Prediction Index-guided group and the standard care group. 19 The fourth and largest study noted no difference between the Hypotension Prediction Index-guided group and the control group in the primary outcome variable: amount of hypotension (time-weighted average MAP less than 65 mmHg).…”
Section: Effect Of Hypotension Prediction Index In Clinical Trialsmentioning
confidence: 99%
“…After these initial results, four randomized controlled trials were published, comparing an HPI-guided hemodynamic treatment protocol group with a standard care control group [ 26 , 32 , 33 , 36 ]. The study by Wijnberge et al [ 26 ] involved 60 patients undergoing major high-risk surgery.…”
Section: Clinical Application Of the Hypotension Prediction Indexmentioning
confidence: 99%
“…Table 1 shows the clinical trials for applying the HPI during various surgeries [6,9,[13][14][15][16][17][18][19]. However, the effectiveness of HPI is still controversial, and conflicting research results have been published [11,13,20,21].…”
Section: Research On the Clinical Application Of The Hpi Algorithmmentioning
confidence: 99%